Digitalpreneur: Realizing of Santripreuneur's Competence in an Independent and Sustainable Economy: Realizing of Santripreuneur's Competence in an Independent and Sustainable Economy - May Shinta Retnowati; Musta’an Al Faruqi (AL-FALAH : Journal of Islamic Economics, 2025)
Purpose: This study aims to existence of santri competence on entrepreneurship at Pesantren or describe santris to be able to compete in the creative economy and make optimal use of digital potential in Pesantrens through digitalpreneurship as a solution to overcome the challenges of the digital technology era. This research focuses on the challenges of Pesantrens in the era of the Industrial Revolution 5.0, including adaptation to digital technology in the face of rapid social and economic changes so that Pesantrens are able to develop creative economy models to support economic independence and sustainability. Design/Method/Approach : The research method used is qualitative. This research obtained data from interviews, observations, and documentation activities sourced from ustadz and santri of Pesantren Cahaya Langit Digital. The data was analyzed descriptively with a grounded theory approach. Findings: Cahaya Langit Digital Pesantren is a pesantren that provides free education for the community. The santris have the competencies of tahfidz, digitalpreneur, and madin (teachers in Qur'an Education for children) around the Pesantren. The competence of santris as digitalpreneurs is a form of success for santris in being economically independent.Originality/Values: The social and economic challenges of Pesantrens in the industrial revolution 5.0 include adaptation to technological changes, the development of santris' digital skills, and creative resource management through programs that are digital skills of santris and can compete in society so that santris and Pesantrens can be economically independent which can provide sustainable economic impact for the community